2010
DOI: 10.1134/s0006297910010013
|View full text |Cite
|
Sign up to set email alerts
|

An overview on nucleases (DNase, RNase, and phosphodiesterase) in snake venoms

Abstract: In this review, we have compiled the data on pharmacological activities associated with endogenous purine release related enzymes-nucleases (DNases, RNases, and phosphodiesterases). The results of studies on toxic effects of these enzymes, emphasizing the future directions in this field, are summarized. One of the major problems facing toxicologists is the identification and characterization of specific venom nucleases since they share similar substrate specificities and biochemical properties. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 57 publications
3
44
2
4
Order By: Relevance
“…This is due to heterogeneity of the chromatographic fraction used therein (Suwansrinon et al, 2007). PDE from snake venoms are mostly composed of single polypeptide chain (Dhananjaya and D'Souza, 2010). Exceptions do exist where PDEs are homodimers or homooligomers with disulfide linkage between the subunits, e.g., PDE from Crotalus ruber ruber is a homodimer joined by disulfide bonds (Mori et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is due to heterogeneity of the chromatographic fraction used therein (Suwansrinon et al, 2007). PDE from snake venoms are mostly composed of single polypeptide chain (Dhananjaya and D'Souza, 2010). Exceptions do exist where PDEs are homodimers or homooligomers with disulfide linkage between the subunits, e.g., PDE from Crotalus ruber ruber is a homodimer joined by disulfide bonds (Mori et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Metal chelators like EDTA, 1,10-phenanthroline and citrate completely inhibit DR-PDE. Zn 2þ is usually critical for the catalytic activity of PDEs (Dhananjaya and D'Souza, 2010). Besides Zn 2þ , several transition metal ions can also activate PDEs from other sources; e.g., cAMP PDE from Mycobacteria contains Fe 2þ and Mn 2þ which are crucial for its activity (Podobnik et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Various enzymes in snake venom, including DNases, RNases, and phosphodiesterases, have endo-or exonuclease activities that can hydrolyze nucleic acids and their derivatives. 22,23 Our previous work has shown that the original aptamer βB-1 was completely degraded by the venom of Naja naja atra. 20 Hence, improving the stability of the aptamer βB-1 in snake venom is important for its diagnostic or therapeutic uses.…”
Section: Introductionmentioning
confidence: 99%